Strategi Peningkatan Daya Dukung Wisata di Kawasan Wisata Lembang - Labibah, Fairuz; Khainur, Puti Nailatulfarihah I.; Furqan, Alhilal (JURNAL NASIONAL PARIWISATA, 2023)
Commonly used tourism carrying capacity assessment methods currently have shortcomings because they still use indicators that cannot be measured, making it difficult to be understood and applied in the form of policies by relevant parties. In addition, some indicators are not collected at all by authorities because they are not considered important or are only relevant for one type of destination and not for other destinations. So ESPON conducted research to develop a new method for assessing the carrying capacity of tourist areas that was implemented in four destinations in Slovenia and Italy. The method was then adapted to be implemented in the Lembang tourism area, and has several stages, namely an overview of tourist destinations, a review of tourist destinations from the point of view of sustainable development and tourism development, data collection of tourist destinations, identification of strengths, weaknesses, opportunities, and threats (SWOT), and strategy formulation. Some of the resulting strategies are utilizing natural and cultural wealth wisely to improve the economy and welfare of the community around the tourist area, involving all parties (managers, government, community and tourists) in maintaining public facilities of tourist attractions, making bad reviews of tourists as an evaluation for tourist attraction managers, especially those related to improving public facilities, protecting natural wealth by giving strict sanctions to people who damage nature in tourist areas, and empowering the community in developing all existing tourist attractions.